Relevansi Media Richness sebagai Upaya Dispendukcapil Surabaya dalam Aktivitas Komunikasi Pemerintahan dan Diseminasi Informasi Adminduk (Universitas 17 Agustus 1945 Surabaya, 2023)
In the digital age, government communication practices can be carried out by leveraging social media. This method is considered to be able to increase interaction between netizens and the government, which then changes the way government public relations communicate with their public. The Surabaya Population and Civil Registration Office (Dispendukcapil) implements this by leveraging two websites and several social media platforms at the same time as a tool to convey population information to its public. This study aims to see how the Surabaya Dispendukcapil utilizes new media as an effort to carry out government communication activities and the dissemination process of information about population administration. This research also intends to describe the diversity of message delivery mediums used by Dispendukcapil Surabaya through the lens of Media Richness theory. Using a qualitative research method, this study shows that the existence of new media forces the Surabaya Dispendukcapil to change its communication style with the Surabaya public. Now, the Surabaya Dispendukcapil staff must not only serve population administration, but must also have the ability to disseminate information by producing website and social media content. However, disseminating information in the digital age requires several skills, such as the ability to package content, the ability to understand the characteristics of content that users are looking for, and the techniques (technologies) used to disseminate information. The Surabaya Dispendukcapil does this by forming a special team of Generation Z workers who create population administration content. Keywords: Desemination Information, Government Communication, New Media, Media Richness